The Influence of Solution Concentration and pH for Removal Indigo Carmine using Banana Stem as a Biosorbent - Rahmiana Zein; Yuliana Arianti; Emriadi Emriadi; Putri Ramadhani; Syiffa Fauzia (Hydrogen: Jurnal Kependidikan Kimia, 2023)
The textile industry is one sector that generates effluent containing a significant quantity of pollutants, including dyes, and thus has an effect on the environment. Synthetic dyes, which are toxic and difficult to degrade, are utilized extensively in the textile industry. Therefore, a new study utilizes banana stems as a cost-effective biosorbent to remove indigo carmine dye. This research aims to investigate the use of banana stem waste as a bisorobent in batch method to adsorption indigo carmine dye. The optimal concentration and pH values are 2 and 900 mg/L, respectively. The interaction between the indigo carmine dye and the banana stems is suggested by the FTIR analysis.  The solution's indigo carmine dye may be adsorbed by banana stem.